2014
DOI: 10.1186/s12917-014-0277-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of dicarboxylic acids and polyphenols to attenuate reticular pH drop and acute phase response in dairy heifers fed a high grain diet

Abstract: BackgroundThe aim of this study was to determine the ability of two feed additives, a fumarate-malate (FM) and a polyphenol-essential oil mixture (PM), in attenuating the drop of ruminal pH and the metabolic and immune response resulting from an excessively high grain diet. Six heifers were used in a 3 × 3 Latin square experiment and fed a low starch (LS) diet for 14 d, followed by a high starch (HS) diet for 8 d (NDF 33.6%, starch 30.0% DM). In the last 5 days of each period, barley meal was added to decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 42 publications
3
24
0
Order By: Relevance
“…organic dicarboxylic acids (O) and polyphenols (P), on the rumen microbiota in dairy heifers fed a high-grain diet. The effects of these additives on reticular pH, VFA, lactate and immune response was published earlier by De Nardi et al [ 23 ]. In this companion study both additives, O and P, attenuated the reticular pH drop due to high-grain feeding wich resulted in 16, 18 and 199 min/d spent below pH 5.6, for O, P and control, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…organic dicarboxylic acids (O) and polyphenols (P), on the rumen microbiota in dairy heifers fed a high-grain diet. The effects of these additives on reticular pH, VFA, lactate and immune response was published earlier by De Nardi et al [ 23 ]. In this companion study both additives, O and P, attenuated the reticular pH drop due to high-grain feeding wich resulted in 16, 18 and 199 min/d spent below pH 5.6, for O, P and control, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study described the effect of organic acid (O) and polyphenols (P) on reticular pH drop and acute phase response in dairy heifers fed a high grain diet [ 23 ]. In this manuscript we report the effects of these supplements on rumen bacterial populations in dairy heifers fed a high-grain diet.…”
Section: Introductionmentioning
confidence: 99%
“…The persistent consumption of a HC diet by dairy animals enhances the production of organic acids and significantly results in a decline in pH values of the rumen and intestine [57]. This decrease in pH due to excessive high concentrate diet [8] may affect the alterations of the type of fermentation [9] and the structure of the microbes in the rumen [10, 11]. Moreover, the decline in pH also perturbs the balance of microbial population in the rumen causing substantial release of free endotoxin (lipopolysaccharide, LPS) from gram-negative bacteria [12].…”
Section: Introductionmentioning
confidence: 99%
“…Possibly, being an element of an immune response to LPS, SARA has been reported to increase the concentration of acute phase proteins in the peripheral blood, such as serum amyloid A (SAA) and haptogloblin (Hp) [2, 12, 14, 17]. The SAA has many functions but mainly alters innate immune responses, particularly in the migration of neutrophils and monocytes, while Hp has anti-inflammatory effects; LPS-binding protein (LBP) is activated by microbial infections and facilitates in the neutralization of LPS and in the triggering the release of pro-inflammatory cytokines, Such as TNF-α, IL-6 and IL-1β [6, 1820]. The innate immune system is the first line of defence against invading pathogens; it involves various types of transmembrane and secreted molecules, recognized as pattern recognition receptors (PRR).…”
Section: Introductionmentioning
confidence: 99%
“…Its nutrient composition and its particle size distribution (Kononoff et al 2003;Marchesini et al 2011) were shown to greatly affect dairy cow dry matter intake (DMI), DM digestibility, site of starch digestion, milk production and quality (Khan et al 2015). Moreover, its composition could affect animal health, due to the variable risk of ruminal acidosis depending on the amount of NDF and starch and on the site of starch degradation (De Nardi et al 2013; Marchesini et al 2013;De Nardi et al 2014). However, the maize silage composition is very variable and is affected by many factors related to its cultivation, including genotype and agronomic conditions (Johnson et al 1999;Khan et al 2015).…”
Section: Introductionmentioning
confidence: 99%